Citra Tubuh dan Presentasi Diri Online di Instagram: Dinamika Identitas Pada Dewasa Awal - Manullang, Patricia Desire Sabatina Lorenza; Sokang, Yasinta Astin (Innovative: Journal Of Social Science Research, 2025)
The phenomenon of social media influencers on Instagram displaying ideal bodies has given rise to the concept of "body goals" and certain beauty standards, which encourage early adults to modify their appearance to gain social recognition through online self-presentation. The objective of this study is to ascertain the correlation between body image and online self-presentation on Instagram among early adults in Jakarta. The present study employed a quantitative correlational approach, with 112 participants aged 18-25 years selected through purposive sampling. The instruments employed in this study were the Multidimensional Body Self Relations Questionnaire Appearance Scale (MBSRQ-AS) and the Self Presentation on Facebook Questionnaire (SPFBQ). The collected data were then subjected to rigorous analysis, which included assessments of normality, linearity, and Spearman correlation tests. The results of the study indicate five positive and three negative relationships between body image dimensions and aspects of online self-presentation. A substantial relationship is identified between affection toward body image and real self, suggesting that individuals who experience more negative feelings toward their bodies exhibit a reduced propensity to present themselves authentically on Instagram.